Trust matters: exploring how video and brand attitudes drive purchase intention in food vlog - Fajri, Muhammad Nur; Wilopo, Wilopo; Nuralam, Inggang Perwangsa (BISMA (Bisnis dan Manajemen), 2025)
This study investigates the effect of food vloggers' content value on viewers' attitudes (video attitude and brand attitude) and purchase intention with trust as a moderating variable. The rise of food vlogging as a digital marketing tool has transformed how consumers engage with culinary content and make purchasing decisions. As viewer trust becomes increasingly important in influencing attitudes and behaviour, understanding content value impacts consumer responses through the S-O-R model is essential for marketers and creators alike. This study targets individuals who actively consume content from three prominent Indonesian food vloggers. Data was collected through an online survey from 335 respondents and analysed using Partial Least Square-Structural Equation Model (PLS-SEM). The results show that informative and entertainment value positively influence video attitude. Video attitude positively influences brand attitude and purchase intention. Trust strengthened the relationship between video attitude and purchase intention, as well as brand attitude and purchase intention. The findings offer insights for marketers and content creators, emphasising the importance of engaging content and trust in shaping consumer behaviour, especially for those interested in exploring Indonesian culinary offerings.